The Dark Side of Television - Drueta, Santiago (2014)
To assume the cultural industries without much thought, like any other industry, would cause enormous difficulties, some of which founded the early debates in the political economy of communication and culture. In this article, I reflect upon the characteristics of these industries and of television in particular with respect to two aspects: First, I observe how much they differ from other industrial processes of production of merchandise, given their characteristics of work that they put in objective terms and their constitution of value. Secondly, although necessarily in a summarized way, I reflect on the limitations of disciplines when it is assumed in such a way it separates its objects form the totality of the social.